Agrobiodiversity and integrated seed systems to improve smallholder livelihoods - López Noriega, Isabel; Otieno, Gloria Atieno; Halewood, Michael (2021)
Crop and tree diversity are essential to agriculture sustainability and food and nutrition security. The diversity of species and varieties that are available for farmers and the ways through which this diversity is made accessible to them depend on seed systems. But what must seed systems be like to enhance agrobiodiversity and smallholders’ livelihoods? Our authors take a look at the strengths and weaknesses of existing seed systems and experiences gained from a ten-year project in five countries on three continents.